Fiber sizing agent, fiber material, molding material, and molded product

By using vinyl ester resin and aqueous media with specific structures, the problem of insufficient shear strength of the fiber bundler interface is solved, and the high bundling of the fiber material and the high strength of the molded product are achieved.

CN115702270BActive Publication Date: 2025-04-04DIC CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202180042028.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-06-23
Filing Date
2021-06-03
Publication Date
2025-04-04
Estimated Expiration
2041-06-03

AI Technical Summary

Technical Problem

The interfacial shear strength of the existing fiber bundling agents in the fiber resin is insufficient, which affects the bundling properties of the fiber material and the strength of the formed product.

Method used

A vinyl ester resin containing alkoxy polyoxyalkylene structure, carbamate bonds, (meth)acryloyl and epoxy groups is used, and the epoxy equivalent and (meth)acryloyl equivalent of the vinyl ester resin are adjusted to improve the interface shear strength.

Benefits of technology

The bundling properties and interface shear strength of the fiber bundling agent are significantly improved, and fiber materials with excellent strength can be produced, suitable for bundling agents such as glass fiber or carbon fiber.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0003993716230000051
    Figure GDA0003993716230000051
  • Figure GDA0003993716230000181
    Figure GDA0003993716230000181
Patent Text Reader

Abstract

Provided are a fiber sizing agent, a fiber material, a molding material, and a molded product, wherein the fiber sizing agent comprises: a vinyl ester resin (A) having an alkoxypolyoxyalkylene structure, a urethane bond, a (meth)acryloyl group, and an epoxy group, and an aqueous medium, wherein the epoxy equivalent of the vinyl ester resin (A) is 3,500 g / equivalent to 11,000 g / equivalent. The fiber sizing agent is excellent in bundling properties and interfacial shear strength between the fiber and the resin, and thus can be suitably used to produce a fiber material capable of imparting excellent strength to a molded product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a fiber sizing agent, a fiber material, a molding material, and a molded product. Background Art

[0002] As automobile parts and aircraft parts that are required to have high strength and excellent durability, fiber-reinforced plastics containing a matrix resin such as epoxy resin or vinyl ester resin (epoxy acrylate) and glass fiber, carbon fiber, etc. are used.

[0003] As the glass fiber or carbon fiber used in the fiber-reinforced plastic, generally, fiber materials obtained by bundling several thousand to several tens of thousands of fibers with a fiber sizing agent are often used from the viewpoint of imparting high strength.

[0004] As the fiber sizing agent, for example, a fiber sizing agent containing a vinyl ester resin having an alkoxy polyoxyalkylene structure and a urethane bond is known (for example, see Patent Document 1). However, although the fiber sizing agent has excellent bundling properties, there is a problem that the interfacial shear strength between the fiber and the resin is insufficient.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: WO2018 / 216457 Summary of the invention

[0008] Problems to be solved by the invention

[0009] The problem to be solved by the present invention is to provide a fiber sizing agent having excellent bundling properties and interfacial shear strength between fibers and resins.

[0010] Technical means of solving problems

[0011] The present inventors have conducted studies to solve the above problems and have found that the above problems can be solved by using a fiber sizing agent containing a vinyl ester resin having a specific structure and an aqueous medium, thereby completing the present invention.

[0012] That is, the present invention relates to a fiber sizing agent, comprising: a vinyl ester resin (A) having an alkoxypolyoxyalkylene structure, a urethane bond, a (meth)acryloyl group, and an epoxy group, and an aqueous medium, wherein the fiber sizing agent is characterized in that the epoxy equivalent of the vinyl ester resin (A) is 3,500 g / equivalent to 11,000 g / equivalent.

[0013] Effects of the Invention

[0014] The fiber sizing agent of the present invention can be used to produce a fiber material capable of imparting excellent strength to a molded product, and has excellent fiber bundling properties, and therefore can be suitably used as a sizing agent for glass fibers, carbon fibers, and the like. DETAILED DESCRIPTION

[0015] The fiber sizing agent of the present invention contains a vinyl ester resin (A) having an alkoxypolyoxyalkylene structure, a urethane bond, a (meth)acryloyl group, and an epoxy group, and an aqueous medium.

[0016] The vinyl ester resin (A) is described below. The vinyl ester resin (A) has an alkoxypolyoxyalkylene structure, and the alkoxypolyoxyalkylene structure is a structure in which one end of a polyoxyalkylene chain is blocked by an alkoxy group.

[0017] Examples of the polyoxyalkylene chain include a polyoxyethylene chain, a polyoxypropylene chain, and a polyoxybutylene chain. These polyoxyalkylene chains are also included in the form of blocks or random arrangements.

[0018] Examples of the alkoxy group blocking the terminal of the polyoxyalkylene chain include a methoxy group, an ethoxy group, a propoxy group, and a butoxy group.

[0019] The alkoxypolyoxyalkylene structure preferably has 35% by mass or more of a structure derived from oxyethylene units in the structure, from the viewpoint of further improving water dispersibility.

[0020] In addition, the alkoxypolyoxyalkylene structure preferably has a number average molecular weight of 300 to 7,000 in terms of further improving water dispersibility.

[0021] The mass ratio of the alkoxypolyoxyalkylene structure in the vinyl ester resin (A) is preferably 3% by mass to 60% by mass, more preferably 10% by mass to 55% by mass, from the viewpoint of further improving water dispersibility.

[0022] The vinyl ester resin (A) has a (meth)acryloyl group, and its (meth)acryloyl group equivalent is preferably 3,500 to 11,000 g / equivalent, more preferably 5,000 to 9,000 g / equivalent, from the viewpoint of improving bundling properties and further improving interfacial shear strength.

[0023] In the present invention, the term "(meth)acryloyl" refers to one or both of acryloyl and methacryloyl, the term "(meth)acrylic acid" refers to one or both of acrylic acid and methacrylic acid, the term "(meth)acrylate" refers to one or both of acrylate and methacrylate, and the term "acid (anhydride)" refers to one or both of acid and acid anhydride.

[0024] The vinyl ester resin (A) has an epoxy group, and its epoxy equivalent is 3,500 to 11,000 g / equivalent, preferably 4,000 to 10,000 g / equivalent, and more preferably 5,000 to 9,000 g / equivalent in terms of further improving the interfacial shear strength.

[0025] Furthermore, the vinyl ester resin (A) preferably has a structure derived from a bisphenol A-type epoxy resin in that the bundling property is improved and a molded product having higher strength can be obtained.

[0026] The weight average molecular weight of the vinyl ester resin (A) is preferably 5,000 to 30,000, more preferably 8,000 to 18,000, from the viewpoint of further improving the bundling property.

[0027] The vinyl ester resin (A) can be obtained, for example, by reacting a urethane resin (a1) having an alkoxypolyoxyalkylene structure and an epoxy group with (meth)acrylic acid and / or (meth)acrylic anhydride (a2).

[0028] The vinyl ester resin (A) can be obtained by setting the equivalent ratio (COOH / EP) of the carboxyl group (COOH) derived from (meth)acrylic acid and / or (meth)acrylic anhydride (a2) to the epoxy group (EP) possessed by the urethane resin (a1) to less than 1. In terms of more efficiently obtaining a fiber sizing agent having excellent interfacial shear strength, the equivalent ratio (COOH / EP) is preferably 0.2 to 0.6, and more preferably 0.3 to 0.5.

[0029] The reaction of the epoxy group of the urethane resin (a1) with the (meth)acrylic acid and / or (meth)acrylic anhydride (a2) is preferably performed using an esterification catalyst at 60° C. to 140° C. A polymerization inhibitor or the like may also be used.

[0030] The urethane resin (a1) has an epoxy group, and the epoxy equivalent of the urethane resin (a1) is preferably in the range of 250 g / equivalent to 2,000 g / equivalent in terms of improving the bundling property and obtaining a molded product with higher strength.

[0031] The urethane resin (a1) can be produced, for example, by reacting a compound (a1-1) having an epoxy group and a hydroxyl group, a polyisocyanate (a1-2), a polyoxyalkylene monoalkyl ether (a1-3), and, if necessary, a polyol (a1-4) other than the compound (a1-1), and a chain extender (a1-5) by a conventionally known method in the absence of a solvent or in the presence of an organic solvent. Specifically, in consideration of safety, the reaction is preferably carried out at a reaction temperature of 50° C. to 120° C. for 1 to 15 hours.

[0032] As the compound (a1-1) having an epoxy group and a hydroxyl group, for example, an epoxy resin having a hydroxyl group can be used.

[0033] As the epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, phenol novolac type epoxy resin, ethylphenol novolac type epoxy resin, butylphenol novolac type epoxy resin, octylphenol novolac type epoxy resin, o-cresol novolac type epoxy resin, cresol novolac type epoxy resin, resorcinol novolac type epoxy resin, bisphenol A novolac type epoxy resin, bisphenol F novolac type epoxy resin, bisphenol AD ​​novolac type epoxy resin, bisphenol S novolac type epoxy resin, etc. can be listed. In terms of improved bundling and the ability to obtain a molded product with higher strength, phenol novolac type epoxy resin, cresol novolac type epoxy resin, or bisphenol A type epoxy resin is preferred, and bisphenol A type epoxy resin is more preferred. Furthermore, these epoxy resins can be used alone or in combination of two or more.

[0034] As the compound (a1-1), it is preferred to use a phenol novolac type epoxy resin having a hydroxyl group, a cresol novolac type epoxy resin having a hydroxyl group, or a bisphenol A type epoxy resin having a hydroxyl group. Among these, a bisphenol A type epoxy resin having a hydroxyl group is more preferred in terms of improved bundling properties and the ability to obtain a molded product with higher strength.

[0035] As the compound (a1-1), it is preferred to use a compound (a1-1) having an epoxy equivalent of 150 g / equivalent to 2,000 g / equivalent, more preferably 150 g / equivalent to 900 g / equivalent, and even more preferably 150 g / equivalent to 500 g / equivalent.

[0036] Regarding the hydroxyl group possessed by the compound (a1-1), in terms of improved bundling properties and the ability to obtain a molded product with higher strength, the hydroxyl group content of the compound (a1-1) is preferably in the range of 5 mol% to 150 mol%, more preferably in the range of 5 mol% to 130 mol%, and even more preferably in the range of 5 mol% to 120 mol%, relative to the total amount of epoxy groups possessed by the urethane resin (a1).

[0037] As the polyisocyanate (a1-2), for example, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, 1-methyl-2,4-phenylene diisocyanate, diisocyanate, 2,4-TDI), 1-methyl-2,6-phenylene diisocyanate (2,6-TDI), 1-methyl-2,5-phenylene diisocyanate, 1-methyl-2,6-phenylene diisocyanate, 1-methyl-3,5-phenylene diisocyanate, 1-ethyl-2,4-phenylene diisocyanate, 1-isopropyl-2,4-phenylene diisocyanate, 1,3-dimethyl-2,4-phenylene diisocyanate, 1,3-dimethyl-4,6-phenylene diisocyanate, 1,4-dimethyl-2,5-phenylene diisocyanate, diethylphenylene diisocyanate, diisopropylphenylene diisocyanate, 1-methyl-3,5-diethylphenylene diisocyanate, 3-methyl-1,5-diethylphenylene-2,4-diisocyanate isocyanate, 1,3,5-triethylbenzene-2,4-diisocyanate, naphthalene-1,4-diisocyanate, naphthalene-1,5-diisocyanate, 1-methyl-naphthalene-1,5-diisocyanate, naphthalene-2,6-diisocyanate, naphthalene-2,7-diisocyanate, 1,1-dinaphthyl-2,2'-diisocyanate, biphenyl-2,4'-diisocyanate, biphenyl-4,4'-diisocyanate, 3,3'-dimethylbiphenyl-4,4'-diisocyanate, diphenylmethane-4,4'-diisocyanate, diphenylmethane-2,2'-diisocyanate, diphenylmethane-2,4-diisocyanate and other aromatic polyisocyanates; tetramethylene diisocyanate, 1,6-hexamethylene diisocyanate (1,6-hexamethylene diisocyanate aliphatic polyisocyanates such as 1,3-cyclopentylene diisocyanate, 1,3-cyclohexylene diisocyanate, 1,4-cyclohexylene diisocyanate, 1,3-bis(isocyanate methyl)cyclohexane, 1,4-bis(isocyanate methyl)cyclohexane, isophorone diisocyanate (isophorone diisocyanate, IPDI), 4,4'-dicyclohexylmethane diisocyanate, 2,4'-dicyclohexylmethane diisocyanate, 2,2'-dicyclohexylmethane diisocyanate, 3,3'-dimethyl-4,4'-dicyclohexylmethane diisocyanate, and trimers thereof. Among these, aromatic polyisocyanates are preferred in terms of further improving interfacial shear strength.

[0038] The polyoxyalkylene monoalkyl ether (a1-3) is a polyoxyalkylene monoalkyl ether (a1-3) represented by the following general formula (1).

[0039] [Chemistry 1]

[0040]

[0041] (Where R 1 is an alkyl group, R 2 is an alkylene group, and n is an integer greater than 1)

[0042] As the polyoxyalkylene monoalkyl ether (a1-3), in terms of further improving storage stability, R in the general formula (1) 1 Preferred is a methyl group, an ethyl group, a propyl group or a butyl group, and more preferred is a methyl group.

[0043] In addition, in terms of further improving storage stability and fiber bundling properties, R in the general formula (1) 2 Preferred is an ethylene group or a propylene group, and more preferred is an ethylene group.

[0044] In terms of further improving storage stability, fiber bundling properties, and strength of the obtained molded product, n in the general formula (1) is preferably an integer of 5 to 150, more preferably an integer of 5 to 100.

[0045] In addition, the polyoxyalkylene monoalkyl ether (a1-3) has a hydroxyl value of preferably 10 to 200, more preferably 15 to 200, from the viewpoint of further improving storage stability.

[0046] As the polyoxyalkylene monoalkyl ether (a1-3), polyoxyethylene monoalkyl ether is more preferably used, and polyoxyethylene monomethyl ether is particularly preferably used, from the viewpoint of further improving storage stability and fiber bundling properties.

[0047] As the polyol (a1-4), for example, polyether polyol, polycarbonate polyol, polyester polyol, ethylene glycol, 1,2-propylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, neopentyl glycol, diethylene glycol, dipropylene glycol, glycerin, trimethylolpropane, acrylic polyol obtained by introducing hydroxyl groups into acrylic copolymers, polybutadiene polyol which is a copolymer of butadiene having hydroxyl groups in the molecule, hydrogenated polybutadiene polyol, partially saponified products of ethylene-vinyl acetate copolymers, etc. can be used.

[0048] As the polyether polyol, for example, a polyether polyol prepared by addition-polymerizing an alkylene oxide using one or more compounds having two or more active hydrogen atoms as an initiator.

[0049] As the polycarbonate polyol, for example, a polycarbonate polyol obtained by reacting a carbonate with a polyol, or a polycarbonate polyol obtained by reacting phosgene with bisphenol A or the like can be used.

[0050] Examples of the polyester polyol include polyester polyols obtained by esterification of low molecular weight polyols and polycarboxylic acids, polyesters obtained by ring-opening polymerization of cyclic ester compounds such as ε-caprolactone and γ-butyrolactone, and copolyesters thereof.

[0051] As the polyether polyol, the polycarbonate polyol, and the aliphatic polyester polyol, those having a number average molecular weight of 300 to 4,000 are preferably used, and those having a number average molecular weight of 500 to 2,000 are more preferably used.

[0052] As the chain extender (a1-5), polyamine or other compounds having active hydrogen atoms can be used.

[0053] Examples of the polyamine include diamines such as ethylenediamine, 1,2-propylenediamine, 1,6-hexamethylenediamine, piperazine, 2,5-dimethylpiperazine, isophoronediamine, 4,4'-dicyclohexylmethanediamine, 3,3'-dimethyl-4,4'-dicyclohexylmethanediamine, and 1,4-cyclohexanediamine; and N-hydroxymethylaminoethylamine, N-hydroxyethylaminoethylamine, and N-hydroxypropylaminopropylamine. , N-ethylaminoethylamine, N-methylaminopropylamine; diethylenetriamine, dipropylenetriamine, triethylenetetramine; hydrazine, N,N'-dimethylhydrazine, 1,6-hexamethylenedihydrazine; succinic acid dihydrazide, adipic acid dihydrazide, glutaric acid dihydrazide, sebacic acid dihydrazide, isophthalic acid dihydrazide; β-aminourea propionic acid hydrazide, 3-aminourea propyl carbazate, amine urea-3-aminoureamethyl-3,5,5-trimethylcyclohexane.

[0054] As the other compounds having active hydrogen, for example, diol compounds such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 1,3-propylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, hexamethylene glycol, sucrose, methylene glycol, glycerol, and sorbitol; phenol compounds such as bisphenol A, 4,4'-dihydroxydiphenyl, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxydiphenyl sulfone, hydrogenated bisphenol A, and hydroquinone; and water can be used.

[0055] The chain extender (a1-5) is preferably used in a range where the equivalent ratio of the amino group of the polyamine to the excess isocyanate group is 1.9 or less (equivalent ratio), and more preferably in a range of 0.3 to 1.0 (equivalent ratio).

[0056] The urethane reaction can also be carried out without a catalyst, and a known catalyst can also be used, for example, tin compounds such as stannous octoate, dibutyltin dilaurate, dibutyltin dimaleate, dibutyltin diphthalate, dibutyltin dimethanolate, dibutyltin diacetylacetate, and dibutyltin diversatate; titanate compounds such as tetrabutyl titanate, tetraisopropyl titanate, and triethanolamine titanate; and other tertiary amine compounds, quaternary ammonium salts, etc.

[0057] The fiber sizing agent of the present invention contains the vinyl ester resin (A) as an essential component, and may contain an epoxy resin (B) and a vinyl ester resin (C) other than the vinyl ester resin (A).

[0058] Examples of the epoxy resin (B) include bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol fluorene type epoxy resin, biscresol fluorene type epoxy resin, phenol novolac type epoxy resin, cresol novolac type epoxy resin, oxazolidinone modified epoxy resin, brominated epoxy resins of these resins, glycidyl ethers of phenols, dipropylene glycol diglycidyl ether, trimethylolpropane triglycidyl ether, diglycidyl ether of alkylene oxide adducts of bisphenol A, glycidyl ethers of polyols such as diglycidyl ether of hydrogenated bisphenol A, 3,4-epoxy-6-methylcyclohexylmethyl Alicyclic epoxy resins such as -3,4-epoxy-6-methylcyclohexanecarboxylate, 1-oxiranyl-3,4-epoxycyclohexane, diglycidyl phthalate, diglycidyl tetrahydrophthalate, diglycidyl-p-hydroxybenzoic acid, diglycidyl diol acid glycidyl ester, tetraglycidyl diaminodiphenylmethane, tetraglycidyl-m-xylene diamine, triglycidyl-p-aminophenol, N,N-diglycidylaniline and other glycidylamines, 1,3-diglycidyl-5,5-dimethylhydantoin, triglycidyl isocyanurate and other heterocyclic epoxy resins, etc. Among these, bifunctional aromatic epoxy resins are preferred, and bisphenol A epoxy resins and bisphenol F epoxy resins are more preferred, in terms of excellent molded product strength, handling properties of the molded material, and fluidity during molding of the molded material. In addition, these epoxy resins may be used alone or in combination of two or more.

[0059] The vinyl ester resin (C) preferably does not have an epoxy group. The vinyl ester resin (C) may be used alone or in combination of two or more.

[0060] The epoxy resin used as the raw material of the vinyl ester resin (C) is preferably a difunctional aromatic epoxy resin, more preferably a bisphenol A epoxy resin and a bisphenol F epoxy resin, in terms of the strength of the molded product, the handleability of the molded material, and the fluidity of the molded material during molding. These epoxy resins may be used alone or in combination of two or more.

[0061] In the present invention, a resin obtained by adding (meth)acrylic acid and / or (meth)acrylic anhydride to at least one epoxy group in an epoxy resin is referred to as a vinyl ester resin.

[0062] Examples of the aqueous medium include water, organic solvents that can be mixed with water, and mixtures thereof. Examples of organic solvents that can be mixed with water include alcohol compounds such as methanol, ethanol, and isopropanol; ketone compounds such as acetone and methyl ethyl ketone; polyalkylene glycol compounds such as ethylene glycol, diethylene glycol, and propylene glycol; alkyl ether compounds of polyalkylene glycols; lactam compounds such as N-methyl-2-pyrrolidone, and the like. In the present invention, only water may be used, or a mixture of water and an organic solvent that can be mixed with water may be used, or only an organic solvent that can be mixed with water may be used. In terms of safety or environmental load, only water or a mixture of water and an organic solvent that can be mixed with water is preferred, and only water is particularly preferred.

[0063] The fiber sizing agent of the present invention contains the vinyl ester resin (A) and an aqueous medium. The vinyl ester resin (A) is preferably an aqueous dispersion dispersed in the aqueous medium.

[0064] The fiber sizing agent of the present invention can be obtained, for example, by mixing a mixed solution of the vinyl ester resin (A) and the vinyl ester resin (C) with an emulsifier and stirring the mixture, then mixing the mixture with the aqueous medium, and removing the solvent as necessary.

[0065] As the emulsifier, for example, polyoxyalkylene alkyl ether, polyoxyalkylene phenyl ether, polyoxyalkylene alkyl phenyl ether, polyoxyalkylene benzyl phenyl ether, polyoxyalkylene styryl phenyl ether, polyoxyalkylene cumyl phenyl ether, polyoxyalkylene naphthyl phenyl ether, polyoxyalkylene fatty acid ester, polyoxyethylene-polyoxypropylene block copolymer, polyethylene glycol, etc. can be cited. Among these, polyoxyalkylene alkyl ether, polyoxyalkylene styryl phenyl ether, polyoxyethylene-polyoxypropylene block copolymer are preferred in terms of further improving the strength of the obtained molded product, and polyoxyalkylene alkyl ether and polyoxyalkylene styryl phenyl ether are more preferred. These emulsifiers can be used alone or in combination of two or more.

[0066] Examples of the polyoxyalkylene alkyl ethers include polyoxyethylene hexyl ether, polyoxyethylene octyl ether, polyoxyethylene nonyl ether, polyoxyethylene lauryl ether, polyoxyethylene stearyl ether, polyoxyethylene eicosyl ether, and polyoxyethylene alkyl ethers such as polyoxyethylene hexyl ether, polyoxyethylene octyl ether, polyoxyethylene nonyl ether, polyoxyethylene stearyl ether, and polyoxyethylene eicosyl ether; polyoxyethylene-polyoxypropylene copolymer alkyl ethers such as polyoxyethylene hexyl ether, polyoxyethylene octyl ether, polyoxyethylene nonyl ether, polyoxyethylene lauryl ether, polyoxyethylene polyoxypropylene copolymer lauryl ether, polyoxyethylene polyoxypropylene copolymer eicosyl ether, and the like. Among these, polyoxyalkylene alkyl ethers having an alkyl group with 8 to 18 carbon atoms such as polyoxyethylene octyl ether, polyoxyethylene nonyl ether, polyoxyethylene lauryl ether, and polyoxyethylene stearyl ether are particularly preferred in terms of improving emulsification. These polyoxyalkylene alkyl ethers may be used alone or in combination of two or more.

[0067] Examples of the polyoxyalkylene styryl phenyl ether include polyoxyethylene monostyryl phenyl ether, polyoxyethylene distyryl phenyl ether, polyoxyethylene tristyryl phenyl ether, and polyoxyethylene styryl phenyl ether having styrene addition mole numbers of 1 to 3, and styryl phenyl ethers of polyoxyethylene polyoxypropylene copolymers having styrene addition mole numbers of 1 to 3. In terms of improving emulsification, polyoxyethylene styryl phenyl ethers having styrene addition mole numbers of 1 to 3 are preferred. These polyoxyalkylene styryl ethers may be used alone or in combination of two or more.

[0068] The polyoxyethylene-polyoxypropylene block copolymer preferably has an average molecular weight of 1,000 to 30,000, more preferably 5,000 to 20,000, in terms of improving emulsification. The polyoxyethylene content is preferably 40% to 90% by mass, more preferably 50% to 80% by mass.

[0069] The mass ratio of the aqueous medium in the fiber sizing agent of the present invention is preferably in the range of 10 to 98 mass %, more preferably in the range of 20 to 90 mass %, from the viewpoint of further improving storage stability and coating workability.

[0070] The mass ratio of the solid content in the fiber sizing agent of the present invention is preferably in the range of 2 to 80 mass %, more preferably in the range of 10 to 70 mass %, from the viewpoint of further improving storage stability and coating workability.

[0071] The fiber sizing agent of the present invention may also contain additives such as silane coupling agents, curing catalysts, lubricants, fillers, thixotropy agents, tackifiers, waxes, heat stabilizers, light stabilizers, fluorescent whitening agents, foaming agents, pH adjusters, leveling agents, gelation inhibitors, dispersion stabilizers, antioxidants, free radical scavengers, heat resistance agents, inorganic fillers, organic fillers, plasticizers, reinforcing agents, catalysts, antibacterial agents, mildew inhibitors, rust inhibitors, thermoplastic resins, thermosetting resins, pigments, dyes, conductivity agents, antistatic agents, moisture permeability enhancers, water repellents, oil repellents, hollow foams, compounds containing crystal water, flame retardants, water absorbents, moisture absorbents, deodorants, foam stabilizers, defoamers, preservatives, algaecides, pigment dispersants, anti-blocking agents, and hydrolysis inhibitors.

[0072] In particular, when the fiber sizing agent of the present invention is used as a sizing agent for glass fibers, it is preferred to use a silane coupling agent in combination from the viewpoint of further improving the bonding strength of the sizing agent to the glass fibers.

[0073] As the silane coupling agent, for example, γ-(2-aminoethyl)aminopropyltrimethoxysilane, γ-(2-hydroxyethyl)aminopropyltrimethoxysilane, γ-(2-aminoethyl)aminopropyltriethoxysilane, γ-(2-hydroxyethyl)aminopropyltriethoxysilane, γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, aminopropylmethyldimethoxysilane, γ-(2-aminoethyl)aminopropylmethyldiethoxysilane, γ-(2-hydroxyethyl)aminopropyltriethoxysilane, )aminopropylmethyldimethoxysilane, γ-(2-hydroxyethyl)aminopropylmethyldiethoxysilane or γ-(N,N-di-2-hydroxyethyl)aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane or γ-(N-phenyl)aminopropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-mercaptophenyltrimethoxysilane, etc.

[0074] The silane coupling agent is preferably used in an amount within a range of 1 to 30 parts by mass based on 100 parts by mass of the total resin components in the fiber sizing agent.

[0075] In addition, the fiber sizing agent of the present invention can also be used in combination with emulsions such as vinyl acetate, ethylene vinyl acetate, acrylic, epoxy, urethane, polyester, polyamide, etc.; latexes such as styrene-butadiene, acrylonitrile-butadiene, acrylic-butadiene, etc., and further water-soluble resins such as polyvinyl alcohol (poval) or cellulose.

[0076] The fiber sizing agent of the present invention can be used for bundling or surface treatment of various fibers for the purpose of preventing fiber breakage and fuzzing of glass fibers, carbon fibers, and the like.

[0077] Examples of fiber materials that can be treated with the fiber sizing agent of the present invention include glass fiber or carbon fiber, silicon carbide fiber, pulp, hemp, cotton, nylon, polyester, acrylic, polyurethane, polyimide, or polyamide fibers including aramid such as Kevlar and Nomex, etc. Among these, glass fiber or carbon fiber is preferably used in terms of high strength.

[0078] As the glass fiber that can be treated with the fiber sizing agent, for example, glass fibers made of alkali glass, low-alkali glass, alkali-free glass, etc. can be used, and it is particularly preferable to use alkali-free glass (E glass) which has little deterioration over time and stable mechanical properties.

[0079] In addition, as the carbon fiber that can be treated with the fiber sizing agent, generally used are polyacrylonitrile-based carbon fibers, pitch-based carbon fibers, etc. Among them, as the carbon fiber, polyacrylonitrile-based carbon fibers are preferably used from the viewpoint of imparting excellent strength.

[0080] In addition, as the carbon fiber, from the viewpoint of imparting more excellent strength, etc., it is preferable to use carbon fiber having a single fiber diameter of 0.5 μm to 20 μm, and it is more preferable to use carbon fiber having a single fiber diameter of 2 μm to 15 μm.

[0081] As the carbon fiber, for example, carbon fibers that have been twisted, spun, woven, or nonwoven can be used. In addition, as the carbon fiber, carbon fibers such as filaments, yarns, rovings, strands, chopped strands, felts, needle punches, fabrics, roving fabrics, and milled fibers can be used.

[0082] As a method of bundling the glass fibers or carbon fibers using the fiber sizing agent of the present invention and forming a film on the surface of the glass fiber bundle or carbon fiber bundle, for example, there can be mentioned a method of uniformly coating the fiber sizing agent on the fiber surface by other known methods such as a kiss coater method, a roller method, an immersion method, a spray method, a brush, etc. When the fiber sizing agent contains an aqueous medium or an organic solvent as a solvent, it is preferably dried by heating using a heating roller, hot air, a hot plate, etc. after the coating.

[0083] The amount of the film formed on the surface of the fibers is preferably 0.1 to 5% by mass, more preferably 0.3 to 1.5% by mass, based on the total mass of the bundled and surface-treated fiber bundle.

[0084] The bundled and surface-treated fiber material of the present invention obtained by the above method can be used as a molding material for producing a high-strength molded product by using it in combination with a matrix resin or the like described below.

[0085] When the fiber material of the present invention is used in combination with a matrix resin to form a molded article, the adhesion at the interface between the fiber and the matrix resin can be significantly improved, thereby increasing the strength of the molded article.

[0086] As the matrix resin used in the molding material of the present invention, for example, a thermosetting resin or a thermoplastic resin can be used. As the thermosetting resin, phenol resin, polyimide resin, bismaleimide resin, unsaturated polyester resin, epoxy resin, vinyl ester resin, vinyl urethane resin, etc. can be used. As the thermoplastic resin, for example, saturated polyester resins such as polyethylene terephthalate or polybutylene terephthalate, polypropylene, polystyrene, polycarbonate, polyphenylene sulfide, polyphenylene oxide, polyamide resins such as 6-nylon and 6,6-nylon, acrylonitrile-styrene copolymer, acrylonitrile-butadiene-styrene copolymer, polyacetal, polyetherimide, polyetheretherketone, etc. can be used.

[0087] The matrix resin is preferably a thermosetting resin, and more preferably a vinyl ester resin or an unsaturated polyester resin, in order to obtain a molded product having higher strength.

[0088] The molding material of the present invention comprises the fiber material and the matrix resin, and optionally a polymerizable monomer, etc., and can be formed into a high-strength molded product by various molding methods such as hand lay-up method, spray-up method, fiber reinforced plastic (FRP) lining method, resin transfer molding method (RTM method), resin injection method (RI method), vacuum assist resin transfer molding method (VARTM method), infusion molding method, press molding method, autoclave molding method, filament winding method, pultrusion molding method, etc. For example, a molding material in the form of a prepreg or sheet molding compound (SMC) can be used for molding.

[0089] The prepreg can be produced, for example, by applying the matrix resin onto release paper, placing a surface-treated fiber material on the applied surface, and, if necessary, performing press impregnation using a roller or the like.

[0090] When the prepreg is produced, it is preferable to use, as the matrix resin, an epoxy resin such as a bisphenol A type epoxy resin, a glycidylamine type epoxy resin such as tetraglycidylaminodiphenylmethane, a novolac type epoxy resin, or a vinyl ester resin.

[0091] The sheet molding compound can be produced, for example, by fully impregnating the surface-treated fiber material with a mixture of the matrix resin and a polymerizable unsaturated monomer such as styrene, and processing the mixture into a sheet. When producing the sheet molding compound, it is preferred to use an unsaturated polyester resin, a vinyl ester resin, or the like as the matrix resin.

[0092] The curing of the molding material is performed, for example, by radical polymerization under pressure or normal pressure, by heating or light irradiation. In this case, a known heat curing agent or light curing agent may be used in combination.

[0093] In addition, examples of the molding material include a molding material obtained by kneading the thermoplastic resin and the surface-treated fiber material under heating, etc. The molding material can be used for secondary processing by, for example, injection molding or the like.

[0094] The prepreg using the thermoplastic resin can be produced, for example, by placing a fiber material subjected to a surface treatment in a sheet form and impregnating the sheet with the molten thermoplastic resin.

[0095] The prepreg obtained using the thermoplastic resin can be used for secondary processing such as laminating one or more sheets, followed by heating and molding under pressure or normal pressure.

[0096] Since the molded product obtained by using the molding material has high strength, it can be used for automobile parts, aircraft parts, wind turbine parts, industrial parts, etc.

[0097] Example

[0098] The present invention is described in more detail below by way of examples: The epoxy equivalent is measured based on Japanese Industrial Standards (JIS) K7236:2001, the acid value is measured based on JIS K0070:1992, and the average molecular weight of the resin is measured under the following gel permeation chromatography (GPC) measurement conditions.

[0099] [GPC measurement conditions]

[0100] Measuring device: High-speed GPC device ("HLC-8220GPC" manufactured by Tosoh Corporation)

[0101] Column: The following columns manufactured by Tosoh Corporation were connected in series and used.

[0102] "TSKgel G5000" (7.8mm I.D. × 30cm) × 1 piece

[0103] "TSKgel G4000" (7.8mm I.D. × 30cm) × 1 piece

[0104] "TSKgel G3000" (7.8mm I.D. × 30cm) × 1 piece

[0105] "TSKgel G2000" (7.8mm I.D. × 30cm) × 1 piece

[0106] Detector: RI (differential refractometer)

[0107] Column temperature: 40℃

[0108] Eluent: tetrahydrofuran (THF)

[0109] Flow rate: 1.0mL / min

[0110] Injection volume: 100 μL (tetrahydrofuran solution with a sample concentration of 4 mg / mL)

[0111] Standard sample: The following monodisperse polystyrene was used to prepare a calibration curve.

[0112] (monodisperse polystyrene)

[0113] "TSKgel Standard Polystyrene A-500" manufactured by Tosoh Corporation

[0114] "TSKgel Standard Polystyrene A-1000" manufactured by Tosoh Corporation

[0115] "TSKgel Standard Polystyrene A-2500" manufactured by Tosoh Corporation

[0116] "TSKgel Standard Polystyrene A-5000" manufactured by Tosoh Corporation

[0117] "TSKgel Standard Polystyrene F-1" manufactured by Tosoh Corporation

[0118] "TSKgel Standard Polystyrene F-2" manufactured by Tosoh Corporation

[0119] "TSKgel Standard Polystyrene F-4" manufactured by Tosoh Corporation

[0120] "TSKgel Standard Polystyrene F-10" manufactured by Tosoh Corporation

[0121] "TSKgel Standard Polystyrene F-20" manufactured by Tosoh Corporation

[0122] "TSKgel Standard Polystyrene F-40" manufactured by Tosoh Corporation

[0123] "TSKgel Standard Polystyrene F-80" manufactured by Tosoh Corporation

[0124] "TSKgel Standard Polystyrene F-128" manufactured by Tosoh Corporation

[0125] "TSKgel Standard Polystyrene F-288" manufactured by Tosoh Corporation

[0126] "TSKgel Standard Polystyrene F-550" manufactured by Tosoh Corporation

[0127] (Synthesis Example 1: Preparation of Aqueous Dispersion of Vinyl Ester Resin (C-1))

[0128] In a four-necked flask equipped with a thermometer, a stirring device, a reflux cooling tube, and a dropping device, 124 parts by mass of polyoxyethylene monoethyl ether ("UNIOX M-550" manufactured by NOF Corporation, hydroxyl value: 100), 99 parts by mass of bisphenol A epoxy resin ("Epiclon 1050" manufactured by DIC Corporation, epoxy equivalent: 477 g / equivalent), and 65 parts by mass of methyl ethyl ketone were added, and the mixture was stirred and dissolved at 40°C. Subsequently, 38 parts by mass of toluene diisocyanate was added at 40°C, and the mixture was reacted at 60°C to 65°C for 6 hours. The infrared absorption spectrum confirmed that the NCO at 2260 cm -1 The disappearance of the characteristic peak.

[0129] Thereafter, the mixture was cooled to 40°C, 15 parts by mass of acrylic acid, 1 part by mass of tert-butylhydroquinone, and 3 parts by mass of 2-methylimidazole were added, and the mixture was heated to 75°C to 80°C under a gas flow of a mixture of nitrogen and air at a ratio of 1:1. The mixture was reacted at 75°C to 80°C for 10 hours, at which time the acid value became less than 1 mgKOH / g, and the reaction was terminated. The weight average molecular weight of the vinyl ester resin (C-1) was 13,000, and the vinyl ester resin had no epoxy group.

[0130] Then, the mixture was cooled to 40°C, 27 parts by mass of polyoxyethylene distyrenated phenyl ether ("EMULGEN A-500" manufactured by Kao Corporation) was added, and the mixture was stirred thoroughly. Then, 850 parts by mass of ion exchange water was added dropwise over 30 minutes, and the mixture was stirred and mixed for 15 minutes. The aqueous dispersion was concentrated by vacuum distillation to obtain an aqueous dispersion of vinyl ester resin (C-1) having a non-volatile component of 30% by mass.

[0131] (Example 1: Production and evaluation of fiber sizing agent (1))

[0132] In a four-necked flask equipped with a thermometer, a stirring device, a reflux cooling tube, and a dropping device, 124 parts by mass of polyoxyethylene monoethyl ether ("UNIOX M-550" manufactured by NOF Corporation, hydroxyl value: 100), 99 parts by mass of bisphenol A epoxy resin ("Epiclon 1050" manufactured by DIC Corporation, epoxy equivalent: 477 g / equivalent), and 65 parts by mass of methyl ethyl ketone were added, and the mixture was stirred and dissolved at 40°C. Subsequently, 38 parts by mass of toluene diisocyanate was added at 40°C, and the mixture was reacted at 60°C to 65°C for 6 hours. The infrared absorption spectrum confirmed that the NCO at 2260 cm -1 The disappearance of the characteristic peak.

[0133] Thereafter, the mixture was cooled to 40°C, 7.5 parts by mass of acrylic acid, 1 part by mass of tert-butylhydroquinone, and 3 parts by mass of 2-methylimidazole were added, and the mixture was heated to 75°C to 80°C under a gas flow of a mixture of nitrogen and air at a ratio of 1:1. The mixture was reacted at 75°C to 80°C for 10 hours, at which time the acid value became 0 mgKOH / g, and the reaction was terminated to obtain a solution of a vinyl ester resin (A-1). The weight average molecular weight of the vinyl ester resin (A-1) was 14,000, and the epoxy equivalent was 7,000 g / equivalent.

[0134] The vinyl ester resin (A-1) had a weight average molecular weight of 14,000 and an epoxy equivalent of 7,000 g / equivalent.

[0135] Then, the mixture was cooled to 40°C, and 27 parts by mass of polyoxyethylene distyrenated phenyl ether ("EMULGEN A-500" manufactured by Kao Corporation) was added, followed by sufficient stirring. Then, 850 parts by mass of ion exchange water was added dropwise over 30 minutes, followed by stirring and mixing for 15 minutes. The aqueous dispersion was concentrated by vacuum distillation to obtain an aqueous dispersion of the vinyl ester resin (A-1) having a nonvolatile content of 30% by mass, i.e., a fiber sizing agent (1).

[0136] [Production of carbon fiber bundles]

[0137] No-size fibers of polyacrylonitrile carbon fibers (single fiber diameter 7 μm, strand strength 4,400 MPa, elastic modulus 235 GPa, 6,000 fibers) are bundled, a fiber sizing agent (1) is diluted with ion exchange water to a non-volatile content of 5% by mass, and the resulting fiber is impregnated with the fiber by an impregnation method. The fiber is twisted with a roller to adjust the amount of active ingredients attached to 1% by mass, and then heat-treated at 150° C. for 30 minutes to obtain a carbon fiber bundle (1) surface-treated with the fiber sizing agent (1).

[0138] [Evaluation of fiber bundling properties]

[0139] Using a TM-200 friction bond tester (manufactured by Daiei Kagaku Seiki Co., Ltd.), the carbon fiber bundle (1) was rubbed 1000 times with a tension of 50 g (reciprocating speed 300 times / minute) via three mirror-finished chrome-plated stainless steel needles arranged in a zigzag pattern, and the fuzzing state of the carbon fiber bundle (1) was visually determined according to the following criteria.

[0140] ○: The surface was the same as before rubbing, and no generation of fuzz was observed.

[0141] ×: Generation of fine hairs was observed.

[0142] [Production of single carbon fiber]

[0143] The non-sized fibers of polyacrylonitrile carbon fibers (single fiber diameter 7 μm, strand strength 4,400 MPa, elastic modulus 235 GPa, 6000 fibers) were impregnated with a fiber sizing agent (1) diluted with ion exchange water to a non-volatile component content of 5% by mass, and then twisted with a roller to adjust the amount of active ingredient attached to 1% by mass, and then the single carbon fibers were taken out.

[0144] [Preparation of matrix resin]

[0145] To 100 parts by mass of a vinyl ester resin solution ("EXDHOMA 9102-01NP" manufactured by DIC Materials Co., Ltd.), 0.5 parts by mass of 6% cobalt naphthenate and 1.0 parts by mass of methyl ethyl ketone peroxide ("PERMEK N" manufactured by NOF Corporation) were added to obtain a matrix resin.

[0146] [Evaluation of interface shear strength]

[0147] The interfacial shear strength between the fiber and the resin was evaluated by the micro droplet method using a composite material interface property evaluation device ("HM410" manufactured by Toei Industry Co., Ltd.).

[0148] A matrix resin was attached to the obtained single carbon fiber to form droplets, which were cured at 25°C for 12 hours and then at 60°C for 3 hours to obtain a sample for measurement. The maximum pultrusion load F (mN) when the resin was pultruded from the fiber of the sample was measured, and the interfacial shear strength τ (MPa) was calculated by the following formula.

[0149] τ=F / πdL

[0150] (τ: interfacial shear strength (MPa), F: maximum pultrusion load (mN), d: fiber diameter (μm), L: droplet axis length (μm))

[0151] ◎: Interface shear strength is 30MPa or more

[0152] ○: Interface shear strength is 20 MPa or more and less than 30 MPa

[0153] ×: Interface shear strength is less than 20Mpa

[0154] (Example 2: Production and evaluation of fiber sizing agent (2))

[0155] In a four-necked flask equipped with a thermometer, a stirring device, a reflux cooling tube, and a dropping device, 124 parts by mass of polyoxyethylene monoethyl ether ("UNIOX M-550" manufactured by NOF Corporation, hydroxyl value: 100), 99 parts by mass of bisphenol A epoxy resin ("Epiclon 1050" manufactured by DIC Corporation, epoxy equivalent: 477 g / equivalent), and 65 parts by mass of methyl ethyl ketone were added, and the mixture was stirred and dissolved at 40°C. Subsequently, 38 parts by mass of trimethylhexamethylene diisocyanate was added at 40°C, and the mixture was reacted at 60°C to 65°C for 6 hours. The infrared absorption spectrum confirmed that the NCO at 2260 cm -1 The disappearance of the characteristic peak.

[0156] Thereafter, the mixture was cooled to 40°C, 7.5 parts by mass of acrylic acid, 1 part by mass of tert-butylhydroquinone, and 3 parts by mass of 2-methylimidazole were added, and the mixture was heated to 75°C to 80°C under a gas flow in which nitrogen and air were mixed at a ratio of 1:1. The mixture was reacted at 75°C to 80°C for 10 hours, at which time the acid value became 0 (mgKOH / g), and the reaction was terminated to obtain a vinyl ester resin (A-2). The weight average molecular weight of the vinyl ester resin (A-2) was 13,500, and the epoxy equivalent was 7,300 g / equivalent.

[0157] Then, the mixture was cooled to 40°C, and 27 parts by mass of polyoxyethylene distyrenated phenyl ether ("EMULGEN A-500" manufactured by Kao Corporation) was added, followed by sufficient stirring. Then, 850 parts by mass of ion exchange water was added dropwise over 30 minutes, followed by stirring and mixing for 15 minutes. The aqueous dispersion was concentrated by vacuum distillation to obtain an aqueous dispersion of a vinyl ester resin (A-2) having a nonvolatile content of 30% by mass, i.e., a fiber sizing agent (2).

[0158] Various evaluations were performed in the same manner as in Example 1, except that the fiber sizing agent (1) used in Example 1 was changed to the fiber sizing agent (2).

[0159] (Example 3: Production and evaluation of fiber sizing agent (3))

[0160] In the same manner as in Example 1, a solution of a vinyl ester resin (A-1) was obtained, and then cooled to 40°C, and 465 parts by mass of an aqueous dispersion of an epoxy resin (B-1) ("HYDRAN N-320M" manufactured by DIC Corporation) and 27 parts by mass of polyoxyethylene distyrenated phenyl ether ("EMULGEN A-500" manufactured by Kao Corporation) were added, and stirred thoroughly. Subsequently, 1,000 parts by mass of ion exchange water was added dropwise over 30 minutes, and the mixture was stirred and mixed for 15 minutes. The aqueous dispersion was concentrated by vacuum distillation to obtain an aqueous dispersion of a vinyl ester resin (A-1) and an epoxy resin (B-1) having a non-volatile component of 30% by mass, namely a fiber sizing agent (3). Vinyl ester resin (A-1) / epoxy resin (B-1) = 25 / 75 (mass ratio).

[0161] Various evaluations were performed in the same manner as in Example 1, except that the fiber sizing agent (1) used in Example 1 was changed to the fiber sizing agent (3).

[0162] (Example 4: Production and evaluation of fiber sizing agent (4))

[0163] In the same manner as in Example 1, a solution of vinyl ester resin (A-1) was obtained, and then cooled to 40°C, 465 parts by mass of the aqueous dispersion of vinyl ester resin (C-1) obtained in Synthesis Example 1 and 27 parts by mass of polyoxyethylene distyrenated phenyl ether ("EMULGEN A-500" manufactured by Kao Corporation) were added, and stirred thoroughly. Subsequently, 1000 parts by mass of ion exchange water was added dropwise over 30 minutes, and the mixture was stirred and mixed for 15 minutes. The aqueous dispersion was concentrated by vacuum distillation to obtain a fiber sizing agent (4) of a vinyl ester resin (A-1) having a non-volatile component of 30% by mass of the vinyl ester resin (a1-1) and an aqueous dispersion of the vinyl ester resin (C-1). Vinyl ester resin (A-1) / vinyl ester resin (C-1) = 25 / 75 (mass ratio).

[0164] Various evaluations were performed in the same manner as in Example 1, except that the fiber sizing agent (1) used in Example 1 was changed to the fiber sizing agent (4).

[0165] (Comparative Example 1: Evaluation of Fiber Sizing Agent (R1))

[0166] The aqueous dispersion of the vinyl ester resin (C-1) obtained in Synthesis Example 1 was used as a fiber sizing agent (R1).

[0167] Various evaluations were performed in the same manner as in Example 1, except that the fiber sizing agent (1) used in Example 1 was changed to the fiber sizing agent (R1).

[0168] Table 1 shows the evaluation results of Examples 1 to 4 and Comparative Example 1.

[0169] [Table 1]

[0170]

[0171] It was confirmed that the fiber sizing agents of Examples 1 to 4, which are the fiber sizing agents of the present invention, were excellent in fiber bundling properties and interfacial shear strength.

[0172] On the other hand, in Comparative Example 1, a vinyl ester resin having no epoxy group was used instead of the vinyl ester resin (A) which is an essential component of the present invention, and it was confirmed that the interfacial shear strength was insufficient.

Claims

1. A fiber sizing agent, characterized in that The invention comprises: a vinyl ester resin (A) having an alkoxy polyoxyalkylene structure, a urethane bond, a (meth) acryloyl group, and an epoxy group, and an aqueous medium; wherein the epoxy equivalent of the vinyl ester resin (A) is 3,500 g / equivalent to 11,000 g / equivalent. 2 . The fiber sizing agent according to claim 1 , wherein the vinyl ester resin (A) has a structure derived from a bisphenol A type epoxy resin.

3. The fiber sizing agent according to claim 1 or 2, comprising an epoxy resin (B). 4 . The fiber sizing agent according to claim 1 , comprising a vinyl ester resin (C) other than the vinyl ester resin (A).

5. A fiber material, characterized in that The fiber sizing agent according to any one of claims 1 to 4.

6. A forming material, characterized in that Containing: the fiber material according to claim 5 and a thermosetting resin.

7. A molded product, characterized in that: This is a hardened product of the molding material according to claim 6.

Citation Information

Patent Citations

  • Fiber sizing agent, fiber material, molding material and molding

    WO2018216457A1

  • Fiber sizing agent, fiber material, molding material and molding

    CN110662865A